Analisis Keputusan Pembelian Konsumen yang dipengaruhi Promosi dan Brand Image (Studi Kasus Sampo Sunsilk Di Kota Bandung) - Dudung Juhana (Kontigensi : Jurnal Ilmiah Manajemen, 2018)
The development of the consumption sector has a rapid and sizeable upward trend due to consumer’s consumptive tendencies. The role of purchasing decisions is essential. Thus, this research tries to find out the purchasing decisions that are influenced by promotions and brand image. The research method of this study is a survey approach to consumers by using purposive sampling. To process the data, this study uses path analysis. The results find there is a significant influence of promotion and brand image on the decision to buy shampoo in Bandung. This finding indicates the critical role of promotion and brand image in increasing the shampoo purchasing decisions, specifically in Bandung.